Examination of Predation on Early Life Stage Delta Smelt in the San Francisco Estuary Using DNA Diet Analysis. Issue 4 (3rd July 2016) - Schreier, Brian M.; Baerwald, Melinda R.; Conrad, J. Louise; Schumer, Gregg; May, Bernie
Abstract: We examined predation by nonnative Mississippi Silversides Menidia audens, other small fishes, and invertebrates on the early life stages of the endangered Delta Smelt Hypomesus transpacificus, which is endemic to the Sacramento–San Joaquin Delta in California. Mississippi Silversides and other putative predators were collected primarily via boat electrofishing in the northern reaches of the upper San Francisco Estuary, an area targeted for substantial tidal wetland restoration to enhance habitat for Delta Smelt and other endangered fishes. Predators' digestive tracts were removed and analyzed for the presence of Delta Smelt DNA by using quantitative PCR TaqMan assays. Across all sites, 69 of 550 Mississippi Silversides tested positive for Delta Smelt DNA. The number of sampled Mississippi Silversides that were positive for Delta Smelt DNA was significantly greater in offshore habitats than in nearshore habitats. Delta Smelt DNA detection data indicated that a wide variety of other species were also predators of Delta Smelt. Additionally, we used generalized linear modeling to analyze the relationship between Delta Smelt predation detections in Mississippi Silversides and concurrently collected habitat parameters. Turbidity was identified as a significant predictor of predation, as Delta Smelt DNA was detected more often in Mississippi Silverside samples from clearer water. These results suggest that restoration efforts designed to increase turbidity in the estuary may be beneficial in reducing Mississippi Silversides' predatory impacts on Delta Smelt. Received August 24, 2015; accepted February 3, 2016 Published online June 15, 2016